Improving Teaching Efficiency: An Application of QFD and AHP - Anis, Azilah; Islam, Rafikul (2009)
HSBL University College is one of the privately runned institutions of higher learning in Malaysia which offers, among others, various programs in Economics, Accounting and Business Administration. A recent survey conducted by the Faculty of Business (FB) of HSBL found that the students were not fully satisfied in the teaching and learning system of the college. The present work has been carried out to identify the FB students’ requirements to improve the efficacy of the teaching and learning system. Having identified the requirements, a number of lecturers were contacted to extract the design requirements that would address the students’ requirements. The novelty of the paper is that Quality Function Deployment and Analytic Hierarchy process – both have been applied to derive the priorities of the design requirements. The results obtained by the above two methods have shown close resemblance.